Aspek Teologi Al-Asy’ariyah dalam Tafsir Mafâtîh al-Ghaib: Studi atas Pemikiran Fakhruddin Ar-Razi - Pahmi Zakiyudin; Abd. Muid; Nurbaiti (AL-MUTSLA, 2025)
This study examines aspects of Ash'ariyah theology in Fakhruddin Ar-Razi's Tafsîr Mafâtîh al-Ghaib, with the aim of exploring how Ar-Razi integrates ratios and revelations in interpreting Qur'anic verses related to theology. Fakhruddin Ar-Razi is a central figure in the Ash'ariyah theological tradition known for his ability to combine rational and textual approaches in his commentary. In his commentary, Ar-Razi divides the attributes of Allah into two main categories: the nature of salbiyah and the nature of thubutiyah, and explains that Allah's will is absolute and His actions are not bound by time. Ar-Razi also discusses ru'yatullah (seeing Allah), emphasizing that seeing God physically in this world is impossible, but it is possible to do so in the hereafter in a spiritual sense. Regarding the purpose of Allah's actions, Ar-Razi argues that Allah does not have a specific purpose in each of His actions, but that all His actions are based on wisdom and benefits that arise as a natural result of His will. The study also notes how Tafsîr Mafâtîh al-Ghaib combines peripatetic philosophy and Ash'ariyah theology, creating a powerful synthesis between ratio and revelation. Ar-Razi criticized the view of Mu'tazilah, who considered that Allah's actions must have a specific purpose, and asserted that Allah's actions remain legitimate and perfect without a specific purpose. Tafsîr Mafâtîh al-Ghaib is a monumental work in the study of Islamic theology, combining rationality with textual interpretation in understanding the theology of the Qur'an in depth.